2015
DOI: 10.1002/2014rs005431
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric tomography in Bayesian framework with Gaussian Markov random field priors

Abstract: We present a novel ionospheric tomography reconstruction method. The method is based on Bayesian inference with the use of Gaussian Markov random field priors. We construct the priors as a system of stochastic partial differential equations. Numerical approximations of these equations can be represented with linear systems with sparse matrices, therefore providing computational efficiency. The method enables an interpretable scheme to build the prior distribution based on physical and empirical information on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 26 publications
0
34
0
Order By: Relevance
“…There are different algorithms available for ionospheric tomography, e.g., the Algebraic Reconstruction Technique or the Bayesian statistical approach . Our three‐dimensional tomography is based on a constrained least squares method with optimized constraining parameters .…”
Section: ‐D Tomographymentioning
confidence: 99%
“…There are different algorithms available for ionospheric tomography, e.g., the Algebraic Reconstruction Technique or the Bayesian statistical approach . Our three‐dimensional tomography is based on a constrained least squares method with optimized constraining parameters .…”
Section: ‐D Tomographymentioning
confidence: 99%
“…In this article we continue the work presented in (Norberg et al, 2015) and include the ionosonde measurements in the Bayesian statistical inversion approach for ionospheric tomography. For comparison, we analyze the data also with the prior mean taken from the International Reference Ionosphere (IRI) model, and with a zero-mean prior.…”
Section: Introductionmentioning
confidence: 90%
“…(6) only the precision matrix −1 pr (i.e., the inverse of the prior covariance) is required besides the prior mean. In (Norberg et al, 2015) it is shown how the precision matrix of a known covariance can be constructed with a sparse matrix representation with Gaussian Markov random fields. The approach provides us with the interpretation of a probability distribution, yet it keeps the approach computationally feasible, in comparison to operating with full covariance matrices.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are different algorithms available for ionospheric tomography, e.g., the Algebraic Reconstruction Technique [2,10] or the Bayesian statistical approach [3,11]. Our three-dimensional tomography is based on a constrained least squares method with optimized constraining parameters [6,8].…”
Section: -D Tomographymentioning
confidence: 99%